Industrial synthesis and characterization of nanophotocatalysts materials: titania - Ramos Delgado, Norma Alicia de Jesús; Gracia Pinilla, Miguel Ángel; Mangalaraja, Ramalinga Viswanathan; O’Shea, Kevin; Dionysiou, Dionysios D. (De Gruyter, 2016)
Despite the recent synthesis and identification of a diverse set of new nanophotocatalysts that has exploded recently, titanium dioxide (TiO2) remains among the most promising photocatalysts because it is inexpensive, non-corrosive, environmentally friendly, and stable under a wide range of conditions. TiO2 has shown excellent promise for solar cell applications and for remediation of chemical pollutants and toxins. Over the past few decades, there has been a tremendous development of nanophotocatalysts for a variety of industrial applications (i.e. for water purification and reuse, disinfection of water matrices, air purification, deodorization, sterilization of soils). This paper details traditional and new industrial routes for the preparation of nanophotocatalysts and the characterization techniques used to understand the physical chemical properties of them, like surface area, ζ potential, crystal size, and phase crystallographic, morphology, and optical transparency. Finally we present some applications of the industrial nanophotocatalysts.